2020
DOI: 10.1089/omi.2020.0147
|View full text |Cite
|
Sign up to set email alerts
|

Assembly and Annotation of the Nuclear and Organellar Genomes of a Dwarf Coconut (Chowghat Green Dwarf) Possessing Enhanced Disease Resistance

Abstract: Coconut (Cocos nucifera L.), an important source of vegetable oil, nutraceuticals, functional foods, and housing materials, provides raw materials for a repertoire of industries engaged in the manufacture of cosmetics, soaps, detergents, paints, varnishes, and emulsifiers, among other products. The palm plays a vital role in maintaining and promoting the sustainability of farming systems of the fragile ecosystems of islands and coastal regions of the tropics. In this study, we present the genome of a dwarf coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 81 publications
1
5
0
Order By: Relevance
“…Compared to their results, our analysis showed 82.19 % overall masking, with 64.93 % LTR elements, which shows the better efficiency of the repeat library designed. The genome assembly of 'Chowghat Green Dwarf' (Muliyar et al, 2020) had reported 77.29 % repeat masking, of which 58.85 % were LTRs. These results are comparable to the present results of 66.18 % overall masking, comprising 46.89 % LTRs.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to their results, our analysis showed 82.19 % overall masking, with 64.93 % LTR elements, which shows the better efficiency of the repeat library designed. The genome assembly of 'Chowghat Green Dwarf' (Muliyar et al, 2020) had reported 77.29 % repeat masking, of which 58.85 % were LTRs. These results are comparable to the present results of 66.18 % overall masking, comprising 46.89 % LTRs.…”
Section: Discussionmentioning
confidence: 99%
“…The genome was filtered through to uncover 112 nucleotide-binding-site and leucinerich repeat (NBS-LRR) loci, representing six types of resistance genes. The CGD genome contains sequence variance associated with disease resistance, making it a helpful tool for developing genomics-assisted breeding in coconuts [95].…”
Section: Whole Genome Sequencing Effortsmentioning
confidence: 99%
“…Coconut palms are monoic, having both male and female flowers on the same inflorescence, perennial diploids (2n = 32) and the sole species of the genus Cocos . Draft genomes have been published suggesting a genome size of about 1.93 Gb (dwarf coconut) to 2.4 Gb (tall Hainan coconut) and a complex genome structure composed of 50–70% of repetitive sequences, chromosome fractionation and duplication followed by rearrangements 2 , 4 , 8 , 9 . Many studies have been conducted to characterize the genetic diversity of coconut collections, and to understand coconut cultivation history 1 , 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%